Sublethal effects of imidacloprid on targeting muscle and ribosomal protein related genes in the honey bee Apis mellifera L. Issue 1 (December 2017) - Wu, Yan-Yan; Luo, Qi-Hua; Hou, Chun-Sheng; Wang, Qiang; Dai, Ping-Li; Gao, Jing; Liu, Yong-Jun; Diao, Qing-Yun
Abstract A sublethal concentration of imidacloprid can cause chronic toxicity in bees and can impact the behavior of honey bees. The nectar- and water-collecting, and climbing abilities of bees are crucial to the survival of the bees and the execution of responsibilities in bee colonies. Besides behavioral impact, data on the molecular mechanisms underlying the toxicity of imidacloprid, especially by the way of RNA-seq at the transcriptomic level, are limited. We treatedApis mellifera L. with sublethal concentrations of imidacloprid (0.1, 1 and 10 ppb) and determined the effect on behaviors and the transcriptomic changes. The sublethal concentrations of imidacloprid had a limited impact on the survival and syrup consumption of bees, but caused a significant increase in water consumption. Moreover, the climbing ability was significantly impaired by 10 ppb imidacloprid at 8 d. In the RNA-seq analysis, gene ontology (GO) term enrichment indicated a significant down-regulation of muscle-related genes, which might contribute to the impairment in climbing ability of bees. The enriched GO terms were attributed to the up-regulated ribosomal protein genes. Considering the ribosomal and extra-ribosomal functions of the ribosomal proteins, we hypothesized that imidacloprid also causes cell dysfunction. Our findings further enhance the understanding of imidacloprid sublethal toxicity.